(3eMGSHI GdJcGdja GdUfGYjIs - (3YHO GdfGUQ GHQGgje(B, (3fhQs ((3YeGf(B:s (3OGQ GdeSjQI ddfTQ hGdJhRjY(B,s, 2002)
(3ebOeI aj eMGSHI GdJcGdja(B-(3CfhGY GdJcGdja(B-(3YfGUQ GdJcGdja(B-(3bhGFe GdCYeGd(B-(3fXGe JcGdja GdChGeQ GdJTZjdjI(B-(3fXGe JcGdja eQGMd GdJTZjd(B-(3fXQjGJ GdJcGdjas
(3HHdhZQGajG U(B. 262s
Keywords: (3GdJcGdja GdUfGYjIs; (3eMGSHI GdJcGdjas